Influence of NTA and FRCN Pedophilia Messages on the Residents of South-East Nigeria - Chime-Nganya, Chioma Rose (Budapest International Research and Critics University, 2024)
This study investigated the influence of NTA and FRCN pedophilia messages on residents of South-East Nigeria. The study has two objectives and one theoretical framework. It used survey research method in which 384 respondents were reached with a structured questionnaire out of which 375 valid responses were obtained. The data were analysed using descriptive statistics and Chi-Square tests using SPSS 20. The study ascertained that residents of South East Nigeria have low level of exposure to broadcast media messages on pedophilia. Despite this situation; their exposure on pedophilia through media broadcast messages significantly improved their knowledge and preparedness in the fight against the hazard. Based on the findings, the study recommended that broadcast media houses in the sub-region should increase their frequency of reportage of pedophilia so as to raise the level of exposure of residents in the area to messages or information on the subject, among other recommendations.